Do no harm, stay current: immersive trauma continuous medical education for emergency medicine postgraduate trainees - Dazlin Masdiana Sabardin,; Afliza Abu Bakar,; Farrael Mohd Azmin,; Mohd Hisham Mohd Isa,; Shamsuriani Md Jamal,; Faizal Amri Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Continuous medical education (CME) is an essential component of postgraduate education to improve trainees’ competencies level to be at par with the current clinical practice thereby improving overall quality of patient healthcare delivery. As a postgraduate trainee in addition to being a part of hospital workforce, providing a compact CME session is essential albeit the learning challenges. Therefore, a framework for the trauma CME program was developed to integrate trainee-led immersive active learning (AL) activities based on our emergency medicine postgraduate training curriculum. It comprised of three components which were miniconferences on trauma management principles updates; hands-on skill stations session utilizing pre-prepared learning packages, simulated scenarios, manikins and phantoms; and immersive trauma simulation on prehospital response, radio communication and patient resuscitation combined with formative assessments and debriefing session. Google Form platform was used to gather the trainees’ self-appraisals of the learning experience. Feedbacks from the trainees revealed that the sessions were engaging and appropriate to their level of training. In conclusion, by incorporating AL activities into immersive trauma CME, it promotes trainees’ engagement towards teaching and learning activities thus consolidating their knowledge and skills on handling trauma patients.